Pembangunan Healing Garden Berbasis Kebun Hortikultura di Lanskap Pesantren Al-Muhajirin, Kiarapedes, Purwakarta - Prita Indah Pratiwi; Bambang Sulistyantara; Indung Sitti Fatimah; Nizar Nasrullah; Riswandi; Andy Darusalam; Yusuf Dwi Shaka Juliandri; Khansa Aqila Arrahman (Institut Pertanian Bogor, 2025)
The Al-Muhajirin Foundation has an elderly Islamic boarding school located in Abun Bunyamin Mukhtar (ABM)Far m, Gardu Village, Kiarapedes District, Purwakarta Regency. The Islamic boarding school's landscape has 4hectares of agricultural land planted with various horticultural crops, including fruit and vegetable crops.Besides elderly boarding school activities, ABM farm is also used as a venue for management meetings, outingclasses, English camps, tahfidz camps, Friday-Saturday camps, and training for students and administrators. Oneinnovation that can support academic and spiritual activities for users is implementing a healing garden. Thisactivity aims to share knowledge about healing garden and provide healing garden design suggestions of ABMfarm to administrators, students, and the community so that they can apply them in school gardens and theirrespective residential environments. The stages used in this activity are 1) Preparation; 2) Inventory; 3) Analysisand synthesis; 4) Concept development; 5) Design creation; 6) Implementation; and 7) Dissemination. Theresults of the healing garden development is a relaxation garden, a toga garden (family medicinal plants), andan edible garden, are effective in providing a space for discussion, murojaah, horticultural plant cultivation, andrecreation for students, teaching staff, administrators, and visitors. During the construction of garden anddissemination, the community was enthusiastic about planting aromatic plants, listening to the material, activelyasking questions, and answering the pre-test and post-test well. The post-test results showed that the lecturer'sreturn home activity increased the community's knowledge about healing garden.